Anxiety and Stress Levels of Health Workers at Health Centers During the COVID-19 Pandemic - Amalia Gandasari (Safety and Health for Medical Workers, 2024)
Introduction; The COVID-19 outbreak has presented considerable obstacles for healthcare professionals, impacting their mental health with heightened levels of anxiety and stress. This research aims to comprehensively examine the anxiety and work-related stress encountered by healthcare workers at Puskesmas (Community Health Centers) amid the pandemic. Menthod; Employing a descriptive survey approach, 200 respondents from diverse healthcare roles across 15 health centers in Semarang City were surveyed using the Depression Anxiety Stress Scale 42 (DASS-42) and The Workplace Stress Scale (WSS). Utilizing SPSS version 25, the collected data underwent descriptive analysis. Result Innovation; Results indicated that a majority of respondents reported normal anxiety levels, with 17.1% experiencing varying degrees of anxiety, from mild to severe. Contributing factors included inadequate personal protective equipment, heightened workload, and insufficient social support. Conclusion; Psychological frameworks such as Occupational Stress and Adaptation Theory provided valuable insights into understanding and addressing individual responses to workplace stressors. It is imperative to address healthcare workers' anxiety and stress during the COVID-19 crisis to ensure their well-being and service quality. Implications and Theory: Effective interventions like support groups, counseling, and coping training are vital for mitigating adverse effects. This study underscores the necessity of tailored interventions informed by psychological theories, alongside emphasizing the importance of adequate protective gear, workload management, and social support in alleviating healthcare workers' anxiety and stress.